Sistemas de produção de pós-larvas de tilápia do Nilo - Marengoni, Nilton Garcia; Wild, Monique Bayer (Scientia Agraria Paranaensis, 2014)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> <![endif]--> The breeding systems are classified according to the structure and strategy of collecting post-larvae used during the tilapias reproduction. The obtaining post-larvae and fingerlings of tilapia in reproduction may occur in ponds, tanks and hapas through the continuous collection of post-larvae in ponds, total collection of post-larvae in hapas, ponds and tanks, or direct collection eggs in the mouths of females and artificial incubation. The study on methodologies and reproductive managements used is critical to the proper functioning of aquaculture ventures, given the continued growth of tilapia fingerlings and the incessant demand for fingerlings. This review aims to evaluate a set of elements and factors that influence the productivity of Nile tilapia fingerlings in different reproduction systems in order to determine the optimal methodology to be employed, highlighting the scientific and technological advances for the tilapia breeding. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->